PID-Controlled Pyrolysis of Medical Mask Waste for Enhanced Alternative Fuel Production - Lusiani, Cucuk Evi; Dewi, Ernia Novika; Hardjono, Hardjono; Naryono, Eko; Febriani, Nahdiyah Nur; Nurlaila, Istiqomah Hanifa (Jurnal Teknik Kimia dan Lingkungan, 2025)
The escalating volume of plastic-based medical mask waste, exacerbated by the COVID-19 pandemic, presents an urgent environmental challenge that can be addressed through sustainable valorization. This study proposes a novel, integrated approach by evaluating the effectiveness of a Proportional-Integral-Derivative (PID) temperature control system to minimize thermal fluctuations critical for consistent product selectivity of the pyrolysis process. A rigorous comparative evaluation of the Cohen-Coon (CC) and Internal Model Control (IMC) tuning methods demonstrated IMC's superiority, achieving a significantly shorter settling time of 114 minutes and a low overshoot of 0.45, ensuring stable isothermal operation. Pyrolysis process conducted under this optimized control condition (at 250°C for 5 hours) resulted in high liquid fuel yields and improved physical characteristics (density 785.8 kg/m3, viscosity 1.546 cSt). Gas Chromatography-Flame Ionization Detector (GC-FID) confirmed that the liquid fuel exhibits hydrocarbon fractions highly similar to commercial kerosene and diesel. These findings underscore that the precision of the IMC-PID method is the key technical enabler for enhancing both process stability and the subsequent quality and yield of valuable liquid fuel derived from medical mask waste.